Pemanfaatan Ampas Sagu dan Daun Pisang Kering sebagai Media Tanam Jamur Tiram (Pleurotus osteoratus): Utilization of Sago Pulp and Dried Banana Leaves as Growing Media for Oyster Mushrooms (Pleurotus osteoratus) - Widayati, Okti; Tanduk, Mesak; Mual, Carolina Diana (Politeknik Pertanian Bogor, 2024)
Oyster mushrooms are one type of mushroom that is widely cultivated for consumption by Indonesians. Oyster mushrooms can generally grow on agricultural waste containing cellulose and lignin. The content can be obtained and found in materials in the surrounding environment such as sago pulp waste and dried banana leaves. The purpose of the study was to determine the effect of the comparison of sago pulp planting media with dried banana leaves on the growth of oyster mushrooms. Experiment design using Completely Randomized Design with 5 treatments with 4 replications consist of P0 (10 kg of sago pulp and 0 kg of banana leaves), P1 (7,5 kg of sago pulp and 2,5 kg of banana leaves), P2 (5 kg of sago pulp and 5 kg of banana leaves), P3 (2,5 kg of sago pulp and 7,5 kg of banana leaves), and P4 (0 kg of sago pulp and 10 kg of banana leaves). Variables measured include mycelium growing speed, pinhead growing time and number of fruit bodies. The results showed that the comparison of sago pulp planting media and dried banana leaves had a significant effect on the growth speed of mycelium, pinhead growing time, and the number of oyster mushroom fruit bodies.The best results for mycelium growth rate were found in P1 treatment which was 12,13 cm/day, pinhead growth time in P3 treatment was 47,75, and the most fruit bodies in P1 treatment was 6,75 fruit bodies.